The effects of rutin supplement on blood pressure markers, some serum antioxidant enzymes, and quality of life in patients with type 2 diabetes mellitus compared with placebo - Bazyar, Hadi; Zare Javid, Ahmad; Ahangarpour, Akram; Zaman, Ferdows; Hosseini, Seyed Ahmad; Zohoori, Vida; Aghamohammadi, Vahideh; Yazdanfar, Shima; Ghasemi Deh Cheshmeh, Mohammad (Frontiers in Nutrition, 2023)
Background: This trial aimed to investigate the effects of rutin supplement in type 2 diabetes mellitus (T2DM) patients. Methods: In this trial with a double-blind and controlled design, fifty patients were randomly divided into intervention (n = 25) and control groups (n = 25) and were treated with 1 g of rutin or placebo for three months, respectively. At the baseline and end of the intervention, mean arterial pressure (MAP), heart rate (HR), pulse pressure (PP), systolic and diastolic blood pressure (SBP and DBP), serum levels of antioxidant enzymes, such as catalase (CAT), glutathione peroxidase (GPx), and superoxide dismutase (SOD) and quality of life (QOL) parameters, were evaluated. Results: Rutin consumption caused a significant reduction in SBP, DBP, PP, MAP, and HR, with a significant increase in SOD, CAT, and GPx and some QOL parameters (emotional limitations, energy and freshness, mental health, social performance, and general health) compared with baseline (p for all < 0.05). Also, the mean changes of emotional limitations, energy and freshness, mental health, and general health (unadjusted p for all < 0.05) and GPX and SOD (adjusted p for all < 0.05) were significantly higher in the rutin group compared with the placebo group. Although, in the supplement group compared with the placebo group, the mean changes of SBP, DBP, MAP, PP, and HR were significantly lower (adjusted p for all < 0.05). Conclusions: Rutin consumption improved blood pressure, the levels of antioxidant enzymes, and QOL in patients with T2DM.